P169 Effect of macrophage migration inhibitory factor on human macrophages from arthritis patients. (March 2019) - Rakovich, T; Cunningham, C; Ansboro, S; McGarry, T; Veale, DJ; Fearon, U
Abstract : Career situation of first and presenting author: Post-doctoral fellow. Introduction: Macrophage migration inhibitory factor (MIF) is a key regulator of pro-inflammatory cytokines and has been implicated in angiogenesis and pathogenesis of several diseases such as rheumatoid arthritis (RA). Macrophages are considered to be one of the key players in the hyperplastic synovial tissue that invades and degrades adjacent cartilage and bone in patients with inflammatory arthritis. Objectives: In this study a comparative analysis was performed to examine the expression of MIF, and the effect it has on the macrophage polarisation and on the angiogenic and inflammatory mechanisms of macrophages in patients with RA, Psoriatic Arthritis (PsA), Osteoarthritis (OA) and in Arthralgia patients. Methods: PBMCs (Peripheral Blood Mononuclear Cells) were isolated from healthy donors, and patients with OA, RA, PsA and Arthralgia. Primary macrophages (Mfs) were subsequently differentiated and polarised from circulating CD14+ monocytes into M1 and M2 phenotypes. The levels of MIF expression in PBMC, Mf and Synovial tissue was evaluated by real-time-PCR (RT-PCR) and Immunohistochemistry (IHC). The effect of MIF on polarisation of Mfs was investigated by examining M1 and M2 Mf specific markers by RT-PCR and Flow Cytometry. Polarised Mf supernatants were harvested and assayed for soluble MIF by ELISA. The effect of MIF on angiogenic and inflammatory markers (MCP-1, IL-6, IL-8, Ang-2, VEGF, Hif1a, PDGF-B, bFGF, RANTES and ICAM-1) of polarised Mfs was investigated by Real-PCR, Western blot and ELISA. Results: MIF expression was significantly increased in RA tissue compared to OA and PsA. In contrast MIF expression in RA PBMCs was significantly decreased when compared to HC, Arthralgia, and PsA. RA tissue biopsies demonstrated significantly higher MIF expression when compared to PsA, OA, and Arthralgia. In polarised macrophages MIF expression was found to be increased in RA and PsA compared to healthy controls. Addition of rhMIF activated pro-inflammatory and angiogenic responses in unpolarised and polarised HC Mfs with increases in gene expression levels of IL-1β, IL-6, MCP-1, ICAM-1, Hey-1, VEGF and Hif1a. Soluble IL-6 expression was also elevated in M0 macrophages. Conclusions: MIF may have a key role in promoting pathogenesis of RA and has a good potential as a therapeutic for RA. Acknowledgements: Author would like to thank Arthritis Ireland for funding this project. Disclosure of Interest: None declared.